Budaya Makan Bersama dalam Perayaan Pengucapan Syukur Sebagai Tindakan Simbolik Integrasi Sosial di Minahasa Tenggara. - Rivenhard Runturambi (Journal of Education, Humaniora and Social Sciences (JEHSS), 2022)
This study aims to describe the understanding and meaning of the celebration of thanksgiving as a symbolic act of social integration in Southeast Minahasa. For the people of Southeast Minahasa who are increasingly modern, the celebration of thanksgiving marked by eating and drinking together is a hereditary legacy as an expression and overflow of gratitude itself. The research used is qualitative research, people believe that eating together in a celebration is to build memory to maintain a relationship on an ongoing basis as Elizabeth Peres' perspective on "eat feeds memory". The results of the study, it was found that the Southeast Minahasa community used food in a celebration not only to fulfill biological needs but also to build and foster relationships to keep them going. If examined from a historical point of view, eating and drinking in the celebration of thanksgiving is not the center of the celebration in question, but for modern society, based on the results of the analysis, food is more important as the most important part of a celebration. Therefore, a more in-depth study is needed on the concept of the celebration of gratitude as a symbolic act of social integration in Southeast Minahasa.